Suicidality in People With Obsessive-Compulsive Symptoms or Personality Traits - Bowen, Rudy; Rahman, Hiba; Dong, Lisa Yue; Khalaj, Sara; Baetz, Marilyn; Peters, Evyn; Balbuena, Lloyd (Frontiers in Psychiatry, 2019)
Objective: Obsessive-Compulsive Disorder (OCD) and Obsessive-Compulsive Personality Disorder (OCPD) have been reported to be associated with mood instability (MI), depression and suicide-related outcomes. We examined whether obsessive-compulsive symptoms and personality traits as well as obsessional thoughts of death, are associated with suicidal thoughts, non-suicidal self-injury and attempted suicide. Methods: We used data from 7,839 people from the 2000 British Adult Psychiatric Morbidity Survey that elicited symptoms of OCD with a computerized version of the Clinical Interview Schedule—Revised (CIS-R) and traits of OCPD with a self-completed version of the SCID-II. We created a series of logistic regression models, first entering only OCD symptoms and OCPD traits in separate models, to which depression and mood instability (MI) were added. We also examined the relation of obsessional thoughts about death with self-harm in a network analysis model that included the main symptoms of mood instability and depression. Results: OCD symptoms were associated with suicidal thoughts (OR: 1.23, 95% CI: 1.14–1.32), and suicide attempts (OR: 1.13, 95% CI: 1.04–1.24) in the fully-adjusted model. OCPD traits were associated with suicidal thoughts (OR: 1.14, 95% CI: 1.10–1.19), non-suicidal self-injury (OR: 1.14 95% CI: 1.03–1.26), and suicide attempts (OR: 1.09; 1.01–1.17). Depression and MI were both associated with all three suicide-related outcomes. In the network analysis, MI was the most prominent correlate of suicide-related outcomes, being associated with suicidal ideas (partial r = 0.15) and non-suicidal self-injury (partial r = 0.07). Limitation: This was a cross-sectional study that used a single-item measure for mood instability. Conclusions: Obsessive-compulsive symptoms and personality traits are related to suicide-related outcomes independently of depressive symptoms and mood instability. This relationship is not accounted for by obsessional thoughts of death alone.